Intelligente Agenten und das Recht - Gless, Sabine (Robotik und Recht, 2016)
A fundamental concern of law is newly foregrounded by the employment of robots: the most precise allocation of charge. Faced with digitalization the question of the aptness of liability concepts again arises and can be answered in view of ancient history, the foundations of law or current practice.